(untitled) (Tanzania Journal for Population studies and Development, 2024)
Reforestation has been emphasized as an authoritative intervention for climate change mitigation because of its carbon storage potential. Reforestation can also play other frequently overlooked, but important, roles in helping society and ecosystems adapt to climate variability and change. For example, reforestation can amend climate-associated impacts of altered hydrological cycles in watersheds, protect coastal areas from increased storms, and provide habitat to reduce the probability of extinction of species under a changing climate. Consequently, reforestation should be managed with both adaptation and mitigation objectives in mind, so as to maximize synergies among these diverse roles, and to avoid trade-offs in which the achievement of one goal is detrimental to another. Management of increased forest cover must also incorporate measures for reducing the direct and indirect impacts of changing climate on reforestation itself. Here, the focus is on ‘climate-smart reforestation’, defined as reforesting for climate change mitigation and adaptation, while ensuring that the direct and indirect impacts of climate change on reforestation are anticipated and minimized.